Determinants and spatial distribution of institutional delivery in Ethiopia: evidence from Ethiopian Mini Demographic and Health Surveys 2019 - Girma Gilano; Samuel Hailegebreal; Biniyam Tariku Seboka (BMC, 2022)
Plain English summary Maternal and child mortality had drawn the attention of governments and policymakers internationally since 1990s. A lot has been said and tried to reduce maternal and child mortality rates by the government of Ethiopia. Initially, toward the end of MDGs period, the country has been successful in achieving some of the goals related to child and maternal mortality. However, after scene of many implementations, now everything looks downcast again. This fact sparked the need to re-assess the status of the country and provide information for further policy decisions. Currently, we were aimed at providing country representative information from EMDHS data regarding the magnitude, spatial pattern, and predictors of in institutional delivery. Factors like age, highest education level achieved, preceding birth interval, literacy status, wealth status, birth order, regions, and rural residences were all affected institutional delivery. However, since home delivery was higher and more worsen in pastoralist regions in the country, it should draw more attentions to make interventions considering awareness, access, and availability of the services in vital areas.